Implementasi Manajemen Strategi dalam Meningkatkan Mutu Pendidikan - Syafira; Khairani; Nasution, Inom; Annisa, Fella; Zuraira, Tasya; Rahmi, Aulia; Anggara, Aldi Bayu; Gani, Arif Abdul (IKAMAS: Manajemen Pendidikan Islam, 2022)
Strategic management is the implementation of planning, monitoring, analysis, and evaluation carried out on an ongoing basis of all the needs needed by the organization in an effort to achieve its goals. Changes that occur quickly and spontaneously in the organizational environment will require organizations that are able to continuously evaluate strategies. Implementation of strategic management helps organizations to know the current state of the organization, then develop strategies, disseminate them and analyze the effectiveness of the implemented management strategies. This research is motivated by the phenomenon of the quality of education that continues to move and change, and the specifications and qualifications will continue to increase with the times. This study aims to determine the implementation of strategic management in improving the quality of education. This research was conducted at Madrasah Tsanawiyah Swasta IRA Medan.. The approach taken is a qualitative approach. The method used is interview, observation and documentation. The results showed that strategic management at Madrasah Tsanawiyah Swasta IRA Medan had been implemented and was oriented towards improving the quality of education.